2018
DOI: 10.26444/aaem/86336
|View full text |Cite
|
Sign up to set email alerts
|

The association between paracetamol use and the risk of asthma, rhinitis and eczema in the Polish population

Abstract: The use of paracetamol in the last 12 months was associated with a significant dose-dependent increase in the risk of rhinitis and skin allergy symptoms, as demonstrated by the odds ratio. Therefore, frequent paracetamol use may be a risk factor for symptoms of asthma, rhinitis, and skin allergy in the Polish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…For acetaminophen exposure in the past year, the meta-analysis of 20 estimates from 9 studies [13,14,16,17,26,29,30,33,34] (581,072 participants) showed significant associations between acetaminophen exposure and allergic rhinitis (OR: 1.74, 95% CI: 1.48-2.04) ( Fig. 2; Table 2).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…For acetaminophen exposure in the past year, the meta-analysis of 20 estimates from 9 studies [13,14,16,17,26,29,30,33,34] (581,072 participants) showed significant associations between acetaminophen exposure and allergic rhinitis (OR: 1.74, 95% CI: 1.48-2.04) ( Fig. 2; Table 2).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
“…One case-control study [30] resulted in a pooled OR of 2.73 (1.65-4.53), whereas 8 cross-sectional studies [13,14,16,17,26,29,33,34] had a pooled OR of 1.63 (1.37-1.93) (χ 2 = 3.61; p = 0.06; I 2 = 72.3%). Three high-quality studies [13,14,33] had a pooled OR of 1.79 (1.32-2.42), whereas 6 moderate-quality studies [16,17,26,29,30,34] resulted in a pooled OR of 1.71 (1.42-2.05) (χ 2 = 0.07; p = 0.80; I 2 = 0). The test for subgroup differences with adjustment for confounding factors showed significant differences (χ 2 = 11.92; p = 0.0006; I 2 = 91.6%).…”
Section: Acetaminophen Exposure In the Past Yearmentioning
confidence: 99%
See 3 more Smart Citations